Displaced Archives - Lowry, James (2017)
Displaced archives have long been a problem and their existence continues to trouble archivists, historians and government officials. Displaced Archives brings together leading international experts to comprehensively explore the current state of affairs for the first time. Drawing on case studies from around the world, the authors examine displaced archives as a consequence of conflict and colonialism, analysing their impact on government administration, nation building, human rights and justice. Renewed action is advocated through considerations of the legal approaches to repatriation, the role of the international archival community, 'shared heritage' approaches and other solutions. The volume offers new theoretical, technical and political insights and will be essential reading for practitioners, academics and students in the field of archives, cultural property and heritage management, as well as history, politics and international relations.